Carelign: A Novel Handoff System for Medical and Surgical Consultants - Shafer, Brian Michael; Gorry, Thomasine; Tapino, Paul; Airan-Javia, Subha (Journal of Academic Ophthalmology, 2020)
Background Patient handoffs are ubiquitous in hospital settings. Historically, formal handoffs of patient information have been conducted in the inpatient setting mainly by primary teams, as opposed to medical and surgical consultants. Carelign is a software developed by the University of Pennsylvania Health System to function as an interdisciplinary, patient-centered handoff. While mainly utilized by primary teams for work management and transitions, it has been enhanced to include specialty consultant handoff functionality.Objective The aim of this study is to determine whether using Carelign for consultant handoffs improves clinical handoffs in comparison to the prior handoff system (a custom-built handoff report within the electronic health record) used by the Department of Ophthalmology at Penn Presbyterian Medical Center.Methods A 7-item questionnaire assessing the effectiveness, efficiency, accessibility, reliability, communication, and security of the handoff using a 1 to 5 scale was distributed to residents prior to and 6 months subsequent to the implementation of Carelign.Results Users reported a statistically significant increase in Health Insurance Portability and Accountability Act (HIPPA)-compliance (44 vs. 100%, p < 0.0001) and ability to communicate with primary teams (38 vs. 70%, p = 0.019) after implementation of Carelign. There was a trend toward significance with ease of accessing information after switching to Carelign (67 vs. 85%, p = 0.185). There was no statistically significant difference in effectiveness, efficiency, accessibility from home, or reliability of information on handoff after converting to the new system.Conclusion Carelign is perceived to be an effective tool that can be used by consulting providers to ensure HIPPA-compliance and the ability to communicate with primary teams without sacrificing effectiveness, efficiency, accessibility, or reliability.
Keywords: handoff; consultant; inpatient ophthalmology; residency